PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PELANGGAN PADA PT BPW INDOPRIMA EKA CAKRAWALA - JULITA, JULITA; Msi, Heryenzus (LPPM Universitas Putera Batam, 2021)
The main objective of the study was to analyze the Effect of Service Quality and Facility on Customer Satisfaction on Customer at PT BPW Indoprima Eka Cakrawala. In this study there were 120 respondents who were used to be analyzed. Multiple regression analysis was used in this test. The independent variable used is service quality and facility and the dependent variable is customer satisfaction. There are three results in this research that were obtained and it resulted that service quality has a positive and significant effect on customer satisfaction, with a significance level of 0.000 < 0.05. this means the first hypotesis is accepted. Facility has a positive and significant effect on customer satisfaction, with a significance level of 0.000 < 0.05, this means that the second hypothesis is accepted. While simultaneously service quality and facility have a significant effect on customer satisfaction with a significant level of 0.000 < 0.05 this means the third hypothesis is accepted.